2018
DOI: 10.2147/ndt.s188210
|View full text |Cite
|
Sign up to set email alerts
|

Activation of IL-8 and its participation in cancer in schizophrenia patients: new evidence for the autoimmune hypothesis of schizophrenia

et al.

Abstract: To investigate the autoimmune mechanisms of schizophrenia, we explored the relationship between schizophrenia and cancer using gene expression data of peripheral blood mononuclear cells from GSE27383 datasets. Gene screening and enrichment analysis using Gene Set Enrichment Analysis were applied to identify possible connections between schizophrenia and cancer. Real-time PCR (quantitative PCR), Western blotting and immunohistochemistry were performed on the brain tissue from both schizophrenia patients and nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…Such elevated levels of IL-8, IL-6, and TNF-α imply that schizophrenia might represent an autoimmune neuropsychiatric spectrum disorder that may emerge during an autoimmune CNS disease ( 63 ). Furthermore, there may be connections between the overexpression of IL-8 in patients with schizophrenia and cancer ( 64 ). Indeed, an elevation of cytokines may provide insight as to why many patients jointly may have schizophrenia and autoimmune diseases ( 65 , 66 ).…”
Section: Cytokines In Schizophreniamentioning
confidence: 99%
“…Such elevated levels of IL-8, IL-6, and TNF-α imply that schizophrenia might represent an autoimmune neuropsychiatric spectrum disorder that may emerge during an autoimmune CNS disease ( 63 ). Furthermore, there may be connections between the overexpression of IL-8 in patients with schizophrenia and cancer ( 64 ). Indeed, an elevation of cytokines may provide insight as to why many patients jointly may have schizophrenia and autoimmune diseases ( 65 , 66 ).…”
Section: Cytokines In Schizophreniamentioning
confidence: 99%
“…A recent study found that the genes responsible for producing the cytokine Interleukin-8 (IL-8) were highly expressed in people suffering from schizophrenia causing greater production of the cytokine when compared to a control group. The results suggest that IL-8 could be responsible for pathophysiological changes in the brain that occur in people suffering from schizophrenia (L. Xu et al, 2018).…”
Section: Autoimmune Hypothesis Of Schizophreniamentioning
confidence: 99%
“…In addition, substantial proteome changes were observed to implicate various cytokines in sarcoidosis [ 96 ]. It should be noted that there is an inverse correlation between PLLP expression and expression of the genes for certain cytokines and growth factors (IL-1, IL-6, IL-8, and VEGFA), indicating indirectly that PLLP may be involved in regulating expression of these genes [ 83 , 84 , 97 101 ].…”
Section: Plasmolipin Role In Disease Pathogenesismentioning
confidence: 99%